COST AND FINANCIAL ECONOMIC IMPACT IN CATHETER ASSOCIATED URINARY TRACT INFECTION (CAUTI): A SYSTEMATIC REVIEW - Sarah, Fatimah; Puput, Oktaminati (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: Catheter-associated urinary tract infections (CAUTI) was the first condition chosen for nonpayment because of its anticipated effect on large numbers of hospitalizations. The risk of CAUTI is mainly related to the duration of catheterization, occurring at a rate of 5% per day. This study is to identify the cost and financial economic impact of intervention and prevention including an indication of CAUTI, number of events, duration of urinary catheterization, length of stay, the cost for antibiotics and hospitalization cost in catheter-associated urinary tract infection (CAUTI) to reducing the rate and hospital payment. Methods: Systematic Review with PRISMA â P Protocol in 2009 method from a relevant database such as PubMed and ProQuest search engine in 2007 until 2017. Total document selected by full text is 10 article. Results: Based on literature search and screening article after using intervention and prevention strategy for CAUTI in the USA, UK and Thailand have a good impact in the duration of urinary catheterization, length of stay, the cost for antibiotic and hospitalization cost. Some article result that the change in the rate of CAUTI was not significantly different before and after the policy and validity in identifying CAUTI is limited. Conclusions: Cost impact in catheter-associated urinary tract infections (CAUTI) can preventable by reducing unnecessary urinary catheter use (appropriate indication), shortening catheter duration, bladder bundles intervention, supervision, and evaluation of the implementation.Â